Solve for y 5y-7=6y-2

Math
5y-7=6y-2
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 6y from both sides of the equation.
5y-7-6y=-2
Subtract 6y from 5y.
-y-7=-2
-y-7=-2
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 7 to both sides of the equation.
-y=-2+7
Add -2 and 7.
-y=5
-y=5
Multiply each term in -y=5 by -1
Tap for more steps…
Multiply each term in -y=5 by -1.
(-y)⋅-1=5⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=5⋅-1
Multiply y by 1.
y=5⋅-1
y=5⋅-1
Multiply 5 by -1.
y=-5
y=-5
Solve for y 5y-7=6y-2

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top